Diagnosis and Treatment of Right Heart Failure in Pulmonary Vascular Diseases: A National Heart, Lung, and Blood Institute Workshop. (16th June 2021) - Leopold, Jane A.; Kawut, Steven M.; Aldred, Micheala A.; Archer, Stephen L.; Benza, Ray L.; Bristow, Michael R.; Brittain, Evan L.; Chesler, Naomi; DeMan, Frances S.; Erzurum, Serpil C.; Gladwin, Mark T.; Hassoun, Paul M.; et al.
Abstract : Right ventricular dysfunction is a hallmark of advanced pulmonary vascular, lung parenchymal, and left heart disease, yet the underlying mechanisms that govern (mal)adaptation remain incompletely characterized. Owing to the knowledge gaps in our understanding of the right ventricle (RV) in health and disease, the National Heart, Lung, and Blood Institute commissioned a working group to identify current challenges in the field. These included a need to define and standardize normal RV structure and function in populations; access to RV tissue for research purposes and the development of complex experimental platforms that recapitulate the in vivo environment; and the advancement of imaging and invasive methodologies to study the RV within basic, translational, and clinical research programs. Specific recommendations were provided, including a call to incorporate precision medicine and innovations in prognosis, diagnosis, and novel RV therapeutics for patients with pulmonary vascular disease.